In Situ Solid Electrolyte Interphase from Spray Quenching on Molten Li: A New Way to Construct High‐Performance Lithium‐Metal Anodes. Issue 3 (21st November 2018) - Liu, Sufu; Xia, Xinhui; Deng, Shengjue; Xie, Dong; Yao, Zhujun; Zhang, Liyuan; Zhang, Shengzhao; Wang, Xiuli; Tu, Jiangping
Abstract: Uncontrollable growth of Li dendrites and low utilization of active Li severely hinder its practical application. Construction of an artificial solid electrolyte interphase (SEI) on Li is demonstrated as one of the most effective ways to circumvent the above problems. Herein, a novel spray quenching method is developed in situ to fabricate an organic–inorganic composite SEI on Li metal. By spray quenching molten Li in a modified ether‐based solution, a homogeneous and dense SEI consisting of organic matrix embedded with inorganic LiF and Li3 N nanocrystallines (denoted as OIFN) is constructed on Li metal. Arising from high ionic conductivity and strong mechanical stability, the OIFN can not only effectively minimize the corrosion reaction of Li, but also greatly suppresses the dendrite growth. Accordingly, the OIFN‐Li anode presents prominent electrochemical performance with an enhanced Coulombic efficiency of 98.15% for 200 cycles and a small hysteresis of <450 mV even at ultrahigh current density up to 10 mA cm −2 . More importantly, during the full cell test with limited Li source, a high utilization of Li up to 40.5% is achieved for the OIFN‐Li anode. The work provides a brand‐new route to fabricate advanced SEI on alkali metal for high‐performance alkali‐metal batteries. Abstract : A novel organic–inorganic composite solid electrolyte interphase on Li metal is constructed in situ by a powerful spray quenching of molten Li in a modified ether‐based solution. Arising from the high ionic conductivity and strong mechanical stability, the artificial OIFN layer can not only minimize the corrosion reaction of Li and greatly suppress the dendrite growth, but also effectively improves the Li‐metal utilization.